DUAL SYSTEM TEACHING OF ENGLISH - Doniyor Tojiboyev Odiljon ugli, (Educational Research in Universal Sciences, 2024)
The main content of this article is that higher education English teachers provide recommendations and methods on how to help students learn English in ability-based classes and how to improve their knowledge. In addition, this article explores effective methods of teaching English in mixed classrooms.